2021
DOI: 10.3389/fphar.2021.769718
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pharmacological Autophagy Regulators of Active Ulcerative Colitis

Abstract: Background: Ulcerative colitis (UC) is a chronic recurrent disease of unknown etiology. Recently, it has been reported that autophagy-related gene polymorphism is closely associated with increased risk of UC, and the therapeutic effect of some UC drugs is mediated by regulating autophagy pathways. This study aims to identify pivotal autophagy-related regulators in UC pathogenesis and provide novel molecular targets for the treatment of active UC.Methods: Gene expression profiles and clinical information of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…Multiple studies have shown an increase in TIMP1 expression in patients with UC. Further, a significant positive correlation was observed between TIMP1 expression and the degree of mucosal injury under an endoscope, C-reactive protein levels, disease, and clinical activity index values (38)(39)(40). These results are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have shown an increase in TIMP1 expression in patients with UC. Further, a significant positive correlation was observed between TIMP1 expression and the degree of mucosal injury under an endoscope, C-reactive protein levels, disease, and clinical activity index values (38)(39)(40). These results are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Receptor-interacting serine/threonine protein kinase 2 ( RIPK2 ) regulates NLRP3 and inflammation [ 25 ], and the NOD/RIPK2 inflammatory signaling pathway has been found to confer susceptibility to osteoarthritis [ 26 ]. CASP1 , encoding caspase 1, is a key component of NLRP3 inflammasomes [ 27 ] and is positively related to active ulcerative colitis [ 28 ]. Our results suggest that PYCARD , RIPK2 , and CASP1 may be involved in regulating DMD-related inflammation via the NLR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies indicated that autophagy is critical for gut homeostasis and intestinal immune function (Larabi et al, 2020). Genome-wide and functional studies identified a role for several autophagy genes in IBD (Qiu et al, 2021; The International IBD Genetics Consortium [IIBDGC] et al, 2012). Thus, manipulating autophagy might be a potential strategy for colitis treatment.…”
Section: Autophagy Influences the Maintenance Of Cellular Homeostasismentioning
confidence: 99%